Validation of the Digital Teaching Competence Questionnaire in Chilean University Teachers - Riquelme-Plaza, Irma (2022)
Objective. Nowadays, university teachers must develop competencies to offer quality education, including digital competence. This study aimed to validate the “Teaching Digital Competence Questionnaire” in the scale of use for the context of higher education in Chile. Method. The method is quantitative, an ex-post factum study. The sample was of 1,122 teachers. Results. The results reveal that the instrument has a high level of validation and reliability. Conclusions. The model achieved through confirmatory factor analysis shows that the factor with greater weight is the maintenance of devices by the university teachers, and the factor with lesser importance is the use of devices in creating digital content. The discussion on the preeminence of the technological dimension over the pedagogical seeks to guide the improvement processes in university teaching.